2019
DOI: 10.1108/jima-08-2018-0140
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality at work and organizational commitment as moderating variables in relationship between Islamic spirituality and OCB IP and influence toward employee performance

Abstract: Purpose The purpose of this study is to analyze the influence of Islamic spirituality toward organizational citizenship behavior from Islamic perspective (OCBIP), influence Islamic spirituality toward OCBIP in which spirituality at work and organizational commitment become mediators and influence of OCBIP toward working performance. Design/methodology/approach The study was categorized as an explanatory research. The setting of the study was the branch office of BRI Syariah in Malang. The population was empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 68 publications
1
31
0
2
Order By: Relevance
“…In recent years, the concept of job satisfaction has received increased attention from scholars and practitioners around the world, who have researched and conducted several social experiments in order to increase employee job satisfaction [1]. Employees are considered part of an organization's assets; therefore, they play a central role for the driving force and leading player of the organization [2]. Therefore, it is important that an organization provides a positive direction to achieve the corporate goals.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the concept of job satisfaction has received increased attention from scholars and practitioners around the world, who have researched and conducted several social experiments in order to increase employee job satisfaction [1]. Employees are considered part of an organization's assets; therefore, they play a central role for the driving force and leading player of the organization [2]. Therefore, it is important that an organization provides a positive direction to achieve the corporate goals.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of OCB on performance is explained by research by Kissi et al (2019). Dharma (2018) and Sani (2019). Munawir (2018) researched universities that showed OCB affects the success of university governance and good performance.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Supported by Ghashghaeinia and Hafezi (2015) who researched on Azad University staff, it also showed that there was a significant positive relationship between organizational culture and OCB. Empirical research that shows the relationship between OCB and performance is described by Kissi et al (2019), Dharma (2018), Munawir et al (2019) and Sani and Maharani (2019).…”
mentioning
confidence: 99%
“…The national banking sector faces more challenges due to its integration in the ASEAN Economic Community (AEC) in 2020 and the rapid development of technology that requires innovation and more flexible services. The banking sector needs to improve the technology, business, human resources, and infrastructure, in order to avoid major losses and anticipate the impact of the AEC (Sani & Ekowati, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the Bank of Jatim Syariah needs to consider these factors before developing its human resource management program. Recently, companies have spent millions of dollars on developing their employees, which, shows that attitudes and performance are key to achieving the estimated goals (Sani & Ekowati, 2019).…”
Section: Introductionmentioning
confidence: 99%